Antimicrobial activities of CuO films deposited on Cu foils by solution chemistry - Nuengruethai Ekthammathat (2018)
Monoclinic CuO thin films on Cu foils were successfully synthesized by a simple wet chemical method in alkaline solution with the pH of 13 at room temperature for different lengths of time. The as-synthesized thin films were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and selected area electron diffraction (SAED). Formation mechanism of the phase and morphologies was also discussed according to the experimental results. In this research, assemblies of pure CuO nanospindles with different orientations containing in the thin film synthesized for 2 weeks with 400 nm and 413 nm violet emissions showed better antimicrobial activity against S. aureus than E. coli. © 2013 Elsevier B.V. All rights reserved.